Research on Visual Localization and Gripping Technology of Robotic Arm Based on Deep Learning - Tang, Jiawei (International Journal of Computer Science and Information Technology, 2024)
With the continuous development of industrial automation, robotic arms are more and more widely used in production lines. In order to realize the autonomous positioning and grasping function of robotic arm, this paper studies the visual positioning and grasping technology of robotic arm based on deep learning. The deep learning algorithm processes and analyzes the image, realizes the automatic identification and localization of the target object, and then guides the robotic arm to carry out accurate grasping. The experimental results show that this technology can effectively improve the positioning accuracy and grasping success rate of the robotic arm, which provides strong support for the intelligent upgrade of industrial automation production lines.